A glass fibre membrane platform for ultra-sensitive detection of cardiac troponin T. Issue 20 (27th September 2017) - Song, Keum-Soo; Nimse, Satish Balasaheb; Sonawane, Mukesh Digambar; Lin, Yahui; Zhou, Zhou; Kim, Taisun
Abstract : A glass fibre membrane platform that allows quantification of circulating cTnT with a LoD of 0.87 pg mL −1 is described. Abstract : A glass fibre membrane platform that allows quantification of circulating cTnT with a LoD of 0.87 pg mL −1 is described. The proposed platform uses a glass fibre membrane, DNA-guided detection method, and antibody-conjugated fluorescent beads for the quantification of cTnT in the analytical detection range of 1–120 pg mL −1 at room temperature in 30 min. Glass fibre membranes were chemically modified to immobilize the oligonucleotide probes that catch a biomolecular complex (FB-dAB-cTnT-cAB-DNA) containing complementary oligonucleotides. There were no interferences from human cTnI, cTnC, skTnT, biotin, and hemoglobin (each 1 μg mL −1 ). The linearity in the serial dilution test of plasma samples indicates that this platform is highly applicable for regular health check-up to assess the risk of AMI and HF.